Ampacet starts up new colour masterbatch line in Luxembourg. Issue 1 (January 2018) - Unknown
Abstract : Global masterbatch producer Ampacet Corp has commenced operations on schedule at its new colour production line in Dudelange, Luxembourg, the site of its European headquarters [see also ADPO, May 2017]. The company says that the new line was developed to optimize lead times and provide additional delivery flexibility for its customers.